Descrição e comparação morfológica da terminália feminina das espécies de Agromyzidae (Diptera: Opomyzoidea) - MONTEIRO, Nilton Juvencio Santiago (Universidade Federal do Pará, 2017)
Agromyzidae is a family of phytophagous flies with great morphological similarity. The male terminalia is the main structure that helps in the identification of the species. However, the female terminalia has been largely neglected by most of the works until now. In this study, the female terminalia of 27 species in 9 genera of Agromyzidae (Japanagromyza Sasakawa, Melanagromyza Hendel, Calycomyza Hendel, Galiomyza Spencer, Liriomyza Mik, Nemorimyza Frey, Phytoliriomyza Hendel, Phytomyza Fallén, Pseudonapomyza Hendel) have been described which were deposited in the Museu de Zoologia da Universidade Federal do Pará (UFPA) and in the Entomological Collection of the Museu Paraense Emílio Goeldi (MPEG). Female abdomens were cleared in 10% KOH, dissected and the female terminalia were drawn using a microscope with camera lucida. The shape of the ninth abdominal segment, the spermathecae and the number of marginal cerdae were important characteristics to identify each species. The shape and length of the egg guides were useful to identify both subfamilies of Agromyzidae (Agromyzinae and Phytomyzinae). Some considerations about similar characteristics have been based in hypothesis for the phylogenetic relationship among genera of the family Agromyzidae. It is expected that the results of this study will be useful for the identification of female specimens from now on.